SIRT1 Knockdown Enhances the Differentiation of Human Embryonic Stem Cells into Pancreatic β Cells - Seo, Nan-Hee (Dev Reprod, 2019)
Nicotinamide is used to maturate pancreatic progenitors from embryonic stem cells (ESCs) into insulin-producing cells (IPCs). It has been known that nicotinamide inhibits the enzymatic activity of SIRT1, an NAD(+)-dependent deacetylase. Here we show that SIRT1 knockdown enhances the differentiation of human ESCs into IPCs. SIRT1 knockdown enhances the clustering size of IPCs and the expression of pancreatic genes including c-peptide, pancreas/duodenum homeobox protein 1 (PDX1), insulin, somatostatin, glucagon and Nkx6.1 in human ESC-derived IPCs. In addition, We found that IPCs differentiated from SIRT1 knockdowned human ESCs have more zinc compared to those from control human ESCs. Our data suggest that SIRT1 negatively regulates the differentiation of β cells from human ESCs.